Comparison between thermodilution and Fick methods for resting and exercise‐induced cardiac output measurement in patients with chronic dyspnea. (29th August 2022) - Desole, Susanna; Obst, Anne; Habedank, Dirk; Opitz, Christian F.; Knaack, Christine; Hortien, Franziska; Heine, Alexander; Stubbe, Beate; Ewert, Ralf
Abstract: Studies comparing thermodilution (TD) and the direct Fick method (dFM) for cardiac output (CO) measurement are rare. We compared CO measurements between TD (2–5 cold water injections), the dFM, and indirect Fick method (iFM) at rest and during exercise, and assessed the effect of averaging different numbers of TD measurements during exercise. This retrospective study included 300 patients (52.3% women, mean age 66 ± 11 years) having pulmonary hypertension (76.0%) or unexplained dyspnea. Invasive hemodynamic and gas exchange parameters were measured at rest (supine; n  = 300) and during unloaded cycling (semi‐supine; n  = 275) and 25‐W exercise (semi‐supine; n  = 240). All three methods showed significant differences in CO measurement (ΔCO) at rest ( p  ≤ 0.001; ΔCO > 1 L/min: 45.0% [iFM vs. dFM], 42.0% [iFM vs. TD], and 45.7% [TD vs. dFM]). ΔCO (TD vs. dFM) was significant during unloaded cycling ( p  < 0.001; ΔCO > 1 L/min: 56.6%) but not during 25‐W exercise ( p  = 0.137; ΔCO > 1 L/min: 52.8%). ΔCO (TD vs. dFM) during 25‐W exercise was significant when using one or two ( p  ≤ 0.01) but not three ( p  = 0.06) TD measurements. Mean ΔCO (TD [≥3 measurements] vs. dFM) was −0.43 ± 1.98 and −0.06 ± 2.29 L/min during unloaded and 25‐W exercise, respectively. Thus, TD and dFM CO measurements are comparable during 25‐W exercise (averaging ≥3 TD measurements), but not during unloaded cycling or at rest. Individual ΔCOs vary substantially and require critical interpretation to avoid CO misclassification.